INTERNALIZATION OF ECOTHEOLOGICAL VALUES THROUGH WASTE-BASED HANDICRAFT LEARNING AMONG PRE-SERVICE MADRASAH IBTIDAIYAH TEACHERS - Pratiwi, Shelly; Asyiah, Nurul; Widowati, Kawuryansih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing complexity of environmental issues requires educational approaches that foster not only environmental knowledge but also ecological values and responsibility. However, higher education learning, particularly in teacher education programs, often remains concept-oriented and has not fully facilitated the internalization of ecotheological values through experiential learning. This study aimed to examine the process of internalizing ecotheological values through waste-based handicraft learning among prospective Madrasah Ibtidaiyah teachers. This research employed a descriptive qualitative approach using a case study method. The participants consisted of 155 fourth-semester students enrolled in the Handicraft course in the Primary Islamic Teacher Education (PGMI) program. Data were collected through observations, interviews, and documentation using triangulation techniques and were analyzed following the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that waste-based handicraft learning implemented through collaborative group work enhanced students' technical skills in transforming various waste materials into aesthetic and functional products while improving collaboration and problem-solving abilities. More importantly, the learning process successfully internalized ecotheological values, including environmental responsibility, ecological awareness, creativity, simplicity, and sustainability. Students developed a new perspective by recognizing waste as a valuable resource and understanding environmental stewardship as part of their spiritual responsibility as khalifah (stewards) of the Earth. Therefore, waste-based handicraft learning represents an effective pedagogical strategy for fostering both ecological and spiritual character among prospective Madrasah Ibtidaiyah teachers.